Media Pembelajaran Tentang Klasifikasi Binatang Berbasis Video Animasi 3 Dimensi di SMP Negeri 2 Wangon - Debby Ummul Hidayah; Pungkas Subarkah (Universitas Bumigora, 2019)
The media is one of the supporting factors that can influence success in education. An education system that only gives lectures tends to make students get bored quickly. Even students are often sleepy when the teacher explains. As a result, the knowledge delivered by the teacher is not optimally absorbed. This proves that students tend to be interested in explanations in the form of visual images. It is hoped that the existence of a 3-dimensional animated video-based media to explain material about animal classification, especially in SMP Negeri 2 Wangon. Media itself is a component that can stimulate a person's mind so they have the desire to learn. The method in making 3-dimensional video animation, through the pre-production, production and post-production stages. In making 3-dimensional video, it explains the classification of animals consisting of pisces, amphibians, reptiles, aves, and mammals. Each is briefly explained and there are examples of each. The final results in the implementation of 3-dimensional video at SMP Negeri 2 Wangon have been successful and enthusiastic students and teachers, hoping that there will be improvements in making 3-dimensional animated videos, especially in animal modeling.